The Utilization of Air Conditioning Heat Waste as Cloth Drying Energy Source - Sarono Widodo; Gatut Rubianto (University of Muhammadiyah Malang, 2021)
Air Conditioning (AC) as an air conditioner has been used on one side only as a room cooling. The cooling process with Air Conditioning produces heat as a result of the work of the condenser component in the AC. This heat can be used as an alternative energy source. This study aims to utilize hot air discharging Air Conditioning as an energy source for drying clothes. This development is based on the Thosiba AC specification. The specification data is used to get the coefficient of performance (COP) and heating effect. Development is also carried out for studies in the form of experiments. The results of the study indicate that the application of AC exhaust heat has the potential to be developed as an alternative energy in the process of drying clothes.